Tropes as Knowledge Figures: A Contribution to Decolonial Thinking [Los Tropos Como Figuraciones de Los Saberes: Una Forma de Contribuir Al Pensamiento Decolonial] - Contreras-Salinas, S; Miranda-Arredondo, P (Universidad de Chile, Facultad de Ciencias Sociales, 2019)
This article proposes to configure knowledge-trope plot as a strategy to uncover colonial ties that persist in the daily lives of situated and incarnated subjects, whose existences develop in conditions of material precariousness, exclusion, exploitation and non-recognition. With a marked epistemic-methodological character, and based on the postulates of the tropology, the notion of trope and knowledge is discussed, as well as pointing out the possible relationships that can occur between them, and finally, in demonstrative terms, to propose a procedure aimed at identifying and analysing the tropes that allow us to reveal colonial ballasts in everyday narratives. The relevance of this proposal is based on the need to construct methodological tools that allow us to understand the principles of decolonial thinking. From there, the trope is proposed as an expression and figurative discussion of knowledge, because it can be used persuasively to affect the way in which the world is inhabited, while at the same time it allows us to understand social action and, consequently, colonial matrices with which we must break. © 2019 Universidad de Chile, Facultad de Ciencias Sociales. All rights reserved.
Keywords: knowledge; colonial veils; tropology; methodology; daily life